2014
DOI: 10.1021/mp500439c
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Nanoparticle Internalization and Transport Across an Intestinal Epithelial Cell Model: Effect of Size and Surface Charge

Abstract: This study investigated the effect of nanoparticle size (50 and 100 nm) and surface charge on their interaction with Caco-2 monolayers as a model of the intestinal epithelium, including cell internalization pathways and the level of transepithelial transport. Initially, toxicity assays showed that cell viability and cell membrane integrity were dependent on the surface charge and applied mass, number, and total surface area of nanoparticles, as tested in two epithelial cell lines, colon carcinoma Caco-2 and ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
219
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(244 citation statements)
references
References 48 publications
15
219
0
2
Order By: Relevance
“…Bannunah et al have demonstrated that positively charged nanoparticles tend to stay inside Caco-2 cells, whereas negatively charge nanoparticles are more efficiently exported from Caco-2 cells. 36) Our results are similar to this observation. In addition, with respect to particle size, we observed that large magnetic liposomes were better retained in Caco-2 cells than small ones (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Bannunah et al have demonstrated that positively charged nanoparticles tend to stay inside Caco-2 cells, whereas negatively charge nanoparticles are more efficiently exported from Caco-2 cells. 36) Our results are similar to this observation. In addition, with respect to particle size, we observed that large magnetic liposomes were better retained in Caco-2 cells than small ones (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…We think this is a reasonable result because cationic nanoparticles have been reported to strongly interact with the negatively charged region of the cell membrane surface via electrostatic forces. 36,38) In addition, we observed that the cellular associated amount of magnetic liposomes at 37°C was much higher than that at 4°C, and the highest quantitative change between 37 and 4°C was observed with magnetic cationic liposomes (Fig. 3).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…While biomedical applications vary in function, what they have in common is the need for a high AuNP delivery rate to be effective. Current design efforts to improve colloid delivery and deposition have focused on material-based approaches, specifically through modification of particle size or surface chemistry (Bannunah et al 2014;Untener et al 2013). While these efforts have been met with moderate success, much work remains to optimize NP deposition and dosimetry (Pal et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…40 Additionally, dynasore, a cell-permeable inhibitor of dynamin, also exhibited a significantly suppressive effect. 41,42 Generally, caveolar, CME, and macropinocytosis are responsible for the internalization of particles of different sizes. 43,44 The pathway studies demonstrated that the endocytosis of SWCNHox may be mediated via multiple mechanisms.…”
mentioning
confidence: 99%